2005
DOI: 10.1007/s11064-004-9680-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of N-myristoyltransferase in Human Brain Tumors

Abstract: N-myristoylation is a process of covalent irreversible protein modification that promotes association of proteins with membranes. Based on our previous findings of elevated N-myristoyltransferase (NMT) activity in colonic epithelial neoplasms that appears at an early stage in colonic carcinogenesis, together with elevated NMT expression in human colorectal and gallbladder carcinomas, we investigated NMT activity and protein expression of NMT1 and NMT2 in human brain tumors and documented elevated NMT activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In human ovarian adenocarcinoma cells, siRNA mediated suppression of Nmt2 expression resulted in a 19-fold increase in apoptosis (Ducker et al, 2005). In addition, the gene has been shown to be inducible by various types of carcinogens such as dioxin (Kolluri et al, 2001) and elevated levels of Nmt2 expression have been described in multiple tumor tissues (Lu et al, 2005; Selvakumar and Sharma, 2007). These data, albeit all generated in malignant cells and tissues, suggest an anti-apoptotic function of the up-regulated expression.…”
Section: Discussionmentioning
confidence: 99%
“…In human ovarian adenocarcinoma cells, siRNA mediated suppression of Nmt2 expression resulted in a 19-fold increase in apoptosis (Ducker et al, 2005). In addition, the gene has been shown to be inducible by various types of carcinogens such as dioxin (Kolluri et al, 2001) and elevated levels of Nmt2 expression have been described in multiple tumor tissues (Lu et al, 2005; Selvakumar and Sharma, 2007). These data, albeit all generated in malignant cells and tissues, suggest an anti-apoptotic function of the up-regulated expression.…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression also occurs relatively early in carcinogenesis, in colonic polyps that are not yet malignant [119]. There is also evidence for the overexpression of NMT in gallbladder and oral squamous cell carcinomas [121,122] and brain tumours [123]. Clegg and co-workers have looked at NMT in mammary epithelial cells and found that proliferative capacity correlated with NMT activity [124].…”
Section: Nmt In Cancermentioning
confidence: 99%
“…Recently, it has been shown that the enzyme myristoylCoA:protein N-myristoyltransferase (NMT) that is involved in the post-translational modification of c-Src is also overexpressed in colon tumor cells and human brain tumors (13)(14)(15)(16)(17). Further, inhibiting the myristoylation of Src in colon cancer cell lines prevents the localization of the kinase to the plasma membrane and results in decreased colony formation and cell proliferation (18).…”
Section: Introductionmentioning
confidence: 99%